Hubungan Panjang Hidung Etnis Minangkabau dengan Tipe Septum Deviasi pada Mahasiswa FK Andalas - Rayhan Al Ichram Novialdi; Eti Yerizel; Al Hafiz (Syntax Idea)
Indonesia's population consists of 633 ethnic groups that have different characters. The Minangkabau have a longer head, nose and chin height than the other two tribes. In addition, septal deviation is defined as the shape of the septum that is not straight in the middle so that it forms a bend in one of the nasal cavities or both nasal cavities resulting in narrowing of the nasal cavity. This study was conducted to examine the relationship between nose length in students of the Faculty of Medicine, Andalas University, Minangkabau ethnicity and the type of nasal septal deviation. This study is a descriptive analytic study using 30 patients. The examinations were Nasoendoscopy and Facial Analysis. Data analysis used statistical test, namely Pearson Chi Square test. Results obtained are the mixed deviation type mean with longer nose length, shorter nose length, and normal nose length; then the type of vertical deviation with longer nose length, shorter nose length and normal nose length respectively were 55.6, 100, 27.3; 44.4, 0 and 68.2 (%). It was found that there was no relationship between nose length in students of the Faculty of Medicine, Andalas University, Minangkabau ethnicity and the type of nasal septal deviation with p value = 0.188 (p > 0.05). Conclusion obtained is that there is no relationship between nose length in students of the Faculty of Medicine, Andalas University, Minangkabau ethnicity and the type of nasal septal deviation.